2020
DOI: 10.1111/iwj.13417
|View full text |Cite
|
Sign up to set email alerts
|

A systematic and psychometric review of tests measuring nurses' wound care knowledge

Abstract: Wound care is an important realm of nurses' clinical responsibilities, and a broad knowledge and range of skills are needed to perform efficient and safe patient care. Nurses' knowledge on this matter can be measured using knowledge tests. This study aims to identify, define, and analyse the knowledge tests developed for the measurement of nurses' wound care knowledge, and to evaluate the psychometric properties of the tests. This study was a systematic literature review. A total of 52 studies and 18 instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…According to a recent systematic literature review [33], of the 18 instruments available, only five had been used more than once and were successful in a psychometric evaluation. The Pressure Ulcer Knowledge Test (PUKT) and the Pressure Ulcer Knowledge Assessment Tool (PUKAT) were the most valid and reliable instruments for measuring nurses' wound care knowledge [33].…”
Section: Of 12mentioning
confidence: 99%
“…According to a recent systematic literature review [33], of the 18 instruments available, only five had been used more than once and were successful in a psychometric evaluation. The Pressure Ulcer Knowledge Test (PUKT) and the Pressure Ulcer Knowledge Assessment Tool (PUKAT) were the most valid and reliable instruments for measuring nurses' wound care knowledge [33].…”
Section: Of 12mentioning
confidence: 99%
“…This indicates that the students might have received more teaching on surgical wound care than other types of wound care. However, as stated in the introduction, previous research on registered nurses' general competence in acute wounds is scarce, because most of the studies on professional competence have focused on chronic wound care ( Kielo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research has also shown that nursing students felt that they did not receive enough education about wound care during their studies ( Kielo et al, 2019 b) and that when they graduated, they did not feel confident in providing wound care ( Stephen-Haynes, 2013 ). Furthermore, most of the previous studies on wound care competence among registered andnursing students focused on pressure ulcers, so there is limited empirical evidence of nursing students' competence in acute wound care or general wound care ( Kielo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…these caring of wound more information and competence, and the care should be based on the evidence available and up-to-date knowledge. With complete awareness , both skill of care and patient privacy can be improved; and when evidence-based interventions are implemented in skills performance , it is possible to reduce the costs of management (2,3) . Clinical Nurses play an important role in the restricted of wound infection and the progressive of healing through the dressing.…”
Section: Introductionmentioning
confidence: 99%